An End To End Ioe-Based Technology Solution for Diabetic Healthcare - Abdulkadhim, Mustafa; ., . (International Journal of Engineering and Technology, 2018)
In the context of keeping the elderly healthy and safe and with the development of the modern small energy efficient technology, with the help of a health monitoring device (HM) as a main activity. The Cloud-based IoT architecture contains a cloud computing and the Internet of Things In order to focus on the advantages that was derived from the complementarities. The sensing services is focused on the development of the sensors data usage and accessibility. beginning from the general scenarios of this service, this paper discusses a Human Machine-oriented Sensing Service scenario with the goal to make the quality of the service and its implementation, taking In consideration the demanding interests of this service which doesn't come only from big medical facilities but also from general practitioners and small clinics. A mathematical model for simulating induced hyperglycemia and hypoglycemia and a smartwatch application is implemented for the patient as well as the health monitoring company (HMC) and the cloud infrastructure for the data to be stored was designed as well as the infrastructure necessary for the patient to run the solution in his/her home.Â Â